Electrophoresis coating process of aluminum fin heat exchanger
Through the electrophoretic coating process, the uniform deposition of epoxy resin or polyurethane resin on aluminum fins has been solved, and the problems of uneven coating thickness and insufficient adhesion in the prior art have been achieved, and high adhesion and durability in complex shapes have been achieved. Improves the anti-corrosion and mildew effect.
Patent Information
- Application Number
- CN202411482235.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When applying anti-corrosion and anti-mildew coating on aluminum fins, there are problems of uneven coating thickness and insufficient adhesion, resulting in a reduction in the protective effect on complex shapes and easy peeling or falling off.
Using electrophoretic coating process, epoxy resin or polyurethane resin coating is deposited through non-ionic cleaning, dilute acid treatment, electrophoresis, and thermal curing at high temperatures to ensure uniformity and adhesion of the coating, and quality inspections are carried out to ensure thickness and adhesion. Focus on the design scope.
The uniform deposition and high adhesion of the coating on complex-shaped aluminum fins is achieved, which improves the durability and corrosion and mildew resistance of the coating, ensures that the coating does not fall or peel off, and enhances quality control and stability.
Smart Images

Figure CN119287480A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrophoresis, in particular to an electrophoresis coating process for an aluminum fin heat exchanger. Background Art
[0002] The fins of air conditioner heat exchangers are usually made of aluminum foil. Before processing, the aluminum foil is rolled into aluminum foil with pre-coated hydrophilic coating on both sides. After punching, the final fins are formed, and the punched surface is exposed aluminum foil. Since the fin cross-section is arranged in multiple rows in parallel, the area is small without any protection and is on the windward side, during the long-term use of the air conditioner, the air inlet will bring various indoor dust, microorganisms, etc. into the heat exchanger. In addition, the deliquescent substances mixed on the surface automatically absorb moisture from the air. The fin cross-section will react with pollutants such as water, air, and microorganisms, causing corrosion and mildew on the punched surface, and alkaline compounds will precipitate on the surface, creating an environment suitable for the growth of mold; it will cause corrosion of the bare aluminum alloy and debonding of the coating on the coated metal for a long time, which will cause the heat exchanger to mold and produce odor.
[0003] In order to solve this technical problem, the prior art CN 118357134 A discloses an application of an anti-corrosion and anti-mildew coating on heat exchanger fins, a preparation method and an air-conditioning heat exchanger. The anti-corrosion and anti-mildew coating is applied to the cross-section of the heat exchanger fins. The cross-section of the heat exchanger fins is a multi-row parallel aluminum foil cross-section formed after punching, which effectively improves the long-term anti-mildew and anti-corrosion performance.
[0004] However, since the aforementioned technical solution is to apply an anti-corrosion and anti-mildew coating, there are differences in the thickness and uniformity of the coating in different parts, especially when brushing or dipping, uneven coating is likely to occur, affecting the anti-corrosion and anti-mildew effects. At the same time, the heat exchange fins of the aforementioned technical solution are a complex geometric shape of multiple rows in parallel, which leads to insufficient adhesion between the physically applied coating and the surface of the substrate. During long-term use, there is a risk of peeling or falling off of the coating, resulting in reduced protective effect. Summary of the invention
[0005] Technical issues solved:
[0006] In view of the shortcomings of the prior art, the present invention provides an electrophoretic coating process for aluminum fin heat exchangers, which has the advantages that the coating arranged on the heat exchange fins with complex shapes will not fall off and peel off, and the coating will not have uneven thickness after adhesion, affecting the anti-corrosion and anti-mildew effects, thereby solving the problems of the above-mentioned technologies.
[0007] Technical solution:
[0008] To achieve the above object, the present invention provides the following technical solution: an electrophoretic coating process for an aluminum fin heat exchanger comprises the following steps:
[0009] Step 1: Pretreatment: Use non-ionic detergent and warm water to clean the aluminum fins to remove oil and dust on the surface; use organic solvent: degreaser, soak or spray to degrease, ensure the surface of the aluminum fins is clean, use dilute acid: sulfuric acid or hydrofluoric acid to treat the aluminum surface, enhance its surface roughness, and improve coating adhesion;
[0010] Step 2: Surface neutralization: Use water to neutralize the surface of the aluminum fins, remove alkaline residues, and clean thoroughly;
[0011] Step 3: Electrophoretic coating: Select epoxy resin or polyurethane resin as the electrophoretic coating, mount the aluminum fin in the electrophoretic tank, connect the power supply, and ensure that the electrodes are well connected;
[0012] Step 4: Electrophoresis process: according to the characteristics of the coating and the aluminum fin, set the voltage: 30V-100V and the current density, and control the electrophoresis time: 10-20 minutes. In the electric field, the coating particles will be evenly deposited on the surface of the aluminum fin to form a dense coating;
[0013] Step 5, curing and drying: After the electrophoresis is completed, take the coated aluminum fins out of the electrophoresis tank, rinse off the excess paint on the surface, place the coated aluminum fins in a well-ventilated environment for 12-24 hours for preliminary drying to remove surface moisture; then put the aluminum fins in an oven and perform thermal curing at 150℃-200℃ for 30-60 minutes;
[0014] Step 6. Quality inspection: Use a coating thickness measuring instrument to check the coating thickness to ensure that it is within the design range: 30-50 microns; use a cross-cut test or peel test to check the adhesion between the coating and the aluminum fin to ensure that there is no peeling; perform a salt spray test and a mold culture test to evaluate the anti-corrosion and anti-mildew properties of the coating.
[0015] Preferably, in step 1, the cleaning agent concentration is 0.5%-1% non-ionic cleaning agent; the cleaning temperature is 60° C.; the cleaning time is 5-10 minutes; the degreasing uses a degreasing agent, the degreasing agent is an organic solvent, and the soaking time is 5 minutes.
[0016] Preferably, the dilute acid in step 1 is sulfuric acid, and the concentration of the sulfuric acid is 10%-20%; the etching time of the sulfuric acid is 2-5 minutes, and the temperature is room temperature to 50°C.
[0017] Preferably, an acid neutralizer is used in step 2, the acid neutralizer is 0.5% sodium hydroxide solution, and the rinsing time is 5 minutes.
[0018] Preferably, the cleaning expression in step 1 is: C 清洗剂 =0.5%-1% non-ionic detergent, T 清洗 =60℃,t 清洗= 5-10 minutes;
[0019] The degreasing expression is: C 脱脂剂 =100% organic solvent, t 脱脂 =5 minutes;
[0020] The acid treatment expression is: C 硫酸 =10%-20%,t 蚀刻 =2-5 minutes, T 蚀刻 =Room temperature - 50°C.
[0021] Preferably, the deposition thickness of the coating in step 4 is calculated as:
[0022]
[0023] Where: d is the deposition thickness of the coating, unit: meter; k is a constant related to the coating properties, coating density and adhesion factors, unit: m 2 / A·s; I is the current, unit: ampere; t is the electrophoresis time, unit: second, s; A is the surface area of the aluminum fin, unit: square meter, m 2 .
[0024] Preferably, the current in step 4 is calculated by Ohm's law of voltage and resistance: Where U is the voltage and R is the total resistance of the electrophoresis tank;
[0025] Combined with the calculation of current, the coating deposition amount is expressed as:
[0026] Preferably, the effect of temperature on the fixed rate in step 5 is calculated as:
[0027]
[0028] Where: k is the reaction rate constant; A is the pre-factor; E a is the activation energy; R is the gas constant; T is the absolute temperature;
[0029] The influence of water evaporation in step 5 is calculated as:
[0030] W(t)=W0e -kt
[0031] Where: W(t) is the water mass at time t; W0 is the initial water mass; k is the evaporation rate constant; t is the time unit: seconds.
[0032] Preferably, the thickness of the coating after curing in step 5 is calculated as:
[0033] df =d0+k·t f
[0034] Where: d f is the final thickness of the coating after curing; d0 is the thickness of the initial coating; t f The time for the curing process.
[0035] Preferably, the mold culture test in step 6 is calculated as:
[0036]
[0037] Where: R fungus Fungal growth inhibition rate; N c is the number of mold in the control group; N t is the number of mold in the test group.
[0038] Compared with the prior art, the present invention provides an electrophoretic coating process for an aluminum fin heat exchanger, which has the following beneficial effects:
[0039] 1. The present invention uses dilute acid: sulfuric acid or hydrofluoric acid to treat the aluminum surface to enhance its surface roughness, uniformly deposits coating particles in an electric field, ensures that the coating thickness and distribution can remain consistent even in the case of complex shapes and fine structures, avoids peeling caused by uneven coating, and performs thermal curing at a high temperature of 150°C-200°C to promote cross-linking between coating molecules and improve the strength and toughness of the coating. This strength makes the coating more durable on fins with complex shapes. The adhesion between the coating and the aluminum fin is confirmed by a cross-cut test or a peeling test to ensure that the coating is within the design range, improves quality control, and further ensures the stability and durability of the coating, achieving the beneficial effect that the coating arranged on the heat exchange fins with complex shapes will not fall off or peel off.
[0040] 2. The present invention uses epoxy resin or polyurethane resin as the electrophoretic coating. Both materials have good adhesion and uniformity. The voltage is set at 30V-100V and the current density is controlled to control the electrophoresis time to 10-20 minutes, so that the coating particles are evenly deposited on the surface of the aluminum fin under the action of the electric field, and thermally cured at a high temperature of 150℃-200℃ to ensure that the coating is evenly heated to form a dense and hardened durable coating, achieving the beneficial effect that the uneven thickness of the coating after adhesion will not affect the anti-corrosion and anti-mildew effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the process steps of the present invention; DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] See also Figure 1 , the electrophoretic coating process of the aluminum fin heat exchanger includes the following steps:
[0044] Step 1: Pretreatment: Use non-ionic detergent and warm water to clean the aluminum fins to remove oil and dust on the surface; use organic solvent: degreaser, soak or spray to degrease, ensure the surface of the aluminum fins is clean, use dilute acid: sulfuric acid or hydrofluoric acid to treat the aluminum surface, enhance its surface roughness, and improve coating adhesion;
[0045] Step 2: Surface neutralization: Use water to neutralize the surface of the aluminum fins, remove alkaline residues, and clean thoroughly;
[0046] Step 3: Electrophoretic coating: Select epoxy resin or polyurethane resin as the electrophoretic coating, mount the aluminum fin in the electrophoretic tank, connect the power supply, and ensure that the electrodes are well connected;
[0047] Step 4: Electrophoresis process: according to the characteristics of the coating and the aluminum fin, set the voltage: 30V-100V and the current density, and control the electrophoresis time: 10-20 minutes. In the electric field, the coating particles will be evenly deposited on the surface of the aluminum fin to form a dense coating;
[0048] Step 5, curing and drying: After the electrophoresis is completed, take the coated aluminum fins out of the electrophoresis tank, rinse off the excess paint on the surface, place the coated aluminum fins in a well-ventilated environment for 12-24 hours for preliminary drying to remove surface moisture; then put the aluminum fins in an oven and perform thermal curing at 150℃-200℃ for 30-60 minutes;
[0049] Step 6. Quality inspection: Use a coating thickness measuring instrument to check the coating thickness to ensure that it is within the design range: 30-50 microns; use a cross-cut test or peel test to check the adhesion between the coating and the aluminum fin to ensure that there is no peeling; perform a salt spray test and a mold culture test to evaluate the anti-corrosion and anti-mildew properties of the coating.
[0050] By selecting epoxy resin or polyurethane resin as the electrophoretic coating, both materials have good adhesion and uniformity: set the voltage to 30V-100V and the current density, control the electrophoresis time to 10-20 minutes, so that the coating particles are evenly deposited on the surface of the aluminum fin under the action of the electric field, and heat cure at a high temperature of 150℃-200℃ to ensure that the coating is evenly heated to form a dense and hardened durable coating.
[0051] Preferably, in step 1, the cleaning agent concentration is 0.5%-1% non-ionic cleaning agent; the cleaning temperature is 60° C.; the cleaning time is 5-10 minutes; the degreasing uses a degreasing agent, the degreasing agent is an organic solvent, and the soaking time is 5 minutes.
[0052] By using dilute acid: sulfuric acid or hydrofluoric acid to treat the aluminum surface, its surface roughness is enhanced, and the coating particles are evenly deposited in the electric field, ensuring that the coating thickness and distribution can remain consistent even in the case of complex shapes and fine structures, avoiding peeling caused by uneven coating, and thermal curing at a high temperature of 150℃-200℃ to promote cross-linking between coating molecules and improve the strength and toughness of the coating. This strength makes the coating more durable on complex-shaped fins. The adhesion between the coating and the aluminum fin is confirmed by a cross-cut test or a peel test to ensure that the coating is within the design range, improve quality control, and further ensure the stability and durability of the coating.
[0053] Preferably, the dilute acid in step 1 is sulfuric acid, and the concentration of the sulfuric acid is 10%-20%; the etching time of the sulfuric acid is 2-5 minutes, and the temperature is room temperature to 50°C.
[0054] Preferably, an acid neutralizer is used in step 2, the acid neutralizer is 0.5% sodium hydroxide solution, and the rinsing time is 5 minutes.
[0055] Preferably, the cleaning expression in step 1 is: C 清洗剂 =0.5%-1% non-ionic detergent, T 清洗 =60℃,t 清洗 = 5-10 minutes;
[0056] The degreasing expression is: 脱脂剂 =100% organic solvent, t 脱脂 =5 minutes;
[0057] The acid treatment expression is: C 硫酸 =10%-20%,t 蚀刻 =2-5 minutes, T 蚀刻 =Room temperature - 50°C.
[0058] Preferably, the deposition thickness of the coating in step 4 is calculated as:
[0059]
[0060] Where: d is the deposition thickness of the coating, unit: meter; k is a constant related to the coating properties, coating density and adhesion factors, unit: m 2 / A·s; I is the current, unit: ampere; t is the electrophoresis time, unit: second, s; A is the surface area of the aluminum fin, unit: square meter, m 2 .
[0061] Preferably, the current in step 4 is calculated by Ohm's law of voltage and resistance: Where U is the voltage and R is the total resistance of the electrophoresis tank;
[0062] Combined with the calculation of current, the coating deposition amount is expressed as:
[0063] Preferably, the effect of temperature on the fixed rate in step 5 is calculated as:
[0064]
[0065] Where: k is the reaction rate constant; A is the pre-factor; E a is the activation energy; R is the gas constant; T is the absolute temperature;
[0066] The influence of water evaporation in step 5 is calculated as:
[0067] W(t)=W0e -kt
[0068] Where: W(t) is the water mass at time t; W0 is the initial water mass; k is the evaporation rate constant; t is the time unit: seconds.
[0069] Preferably, the thickness of the coating after curing in step 5 is calculated as:
[0070] d f =d0+k·t f
[0071] Where: d f is the final thickness of the coating after curing; d0 is the thickness of the initial coating; t f The time for the curing process.
[0072] Preferably, the mold culture test in step 6 is calculated as:
[0073]
[0074] Where: R fungus Fungal growth inhibition rate; Nc is the number of mold in the control group; N t is the number of mold in the test group.
[0075] Through quantitative analysis methods, the curing process and coating performance can be evaluated through specific values. This quantitative analysis helps to understand and optimize process parameters more accurately.
[0076] Using the Arrhenius equation and other mathematical models gives the process a scientific basis. Through these formulas, we can better understand how temperature, time and other factors affect chemical reactions and physical processes.
[0077] By calculating parameters such as reaction rate constants, evaporation rates and coating thickness, the curing process and coating application are optimized to ensure that the quality and performance of the final product meet the expected standards.
[0078] If the coating does not perform as expected, analyzing the parameters in these formulas can help identify potential problems, such as insufficient coating adhesion, and checking factors such as curing temperature, time or initial moisture content.
[0079] By analyzing the activation energy E of different materials a By comparing with the previous factor A, better decisions can be made in material selection to achieve better coating performance.
[0080] Through evaluation methods such as salt spray test and mold culture test, the stability and durability of the coating under different environmental conditions are ensured, increasing the reliability of the product in practical applications.
[0081] Through these scientific calculations and tests, it can be ensured that the thickness, adhesion, and anti-corrosion and anti-mildew properties of the coating meet the design standards, thereby improving the quality of the final product.
[0082] These formulas and calculation methods provide support for data-based decision-making, helping companies make more reasonable adjustments and optimizations in the production process.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. The electrophoretic coating process of aluminum fin heat exchanger is characterized by: The following steps are involved: Step 1: Pretreatment: Use non-ionic detergent and warm water to clean the aluminum fins to remove oil and dust on the surface; use organic solvent: degreaser, soak or spray to degrease, ensure the surface of the aluminum fins is clean, use dilute acid: sulfuric acid or hydrofluoric acid to treat the aluminum surface, enhance its surface roughness, and improve coating adhesion; Step 2: Surface neutralization: Use water to neutralize the surface of the aluminum fins, remove alkaline residues, and clean thoroughly; Step 3: Electrophoretic coating: Select epoxy resin or polyurethane resin as the electrophoretic coating, mount the aluminum fin in the electrophoretic tank, connect the power supply, and ensure that the electrodes are well connected; Step 4: Electrophoresis process: according to the characteristics of the coating and the aluminum fin, set the voltage: 30V-100V and the current density, and control the electrophoresis time: 10-20 minutes. In the electric field, the coating particles will be evenly deposited on the surface of the aluminum fin to form a dense coating; Step 5, curing and drying: After the electrophoresis is completed, take the coated aluminum fins out of the electrophoresis tank, rinse off the excess paint on the surface, place the coated aluminum fins in a well-ventilated environment for 12-24 hours for preliminary drying to remove surface moisture; then put the aluminum fins in an oven and perform thermal curing at 150℃-200℃ for 30-60 minutes; Step 6. Quality inspection: Use a coating thickness measuring instrument to check the coating thickness to ensure that it is within the design range: 30-50 microns; use a cross-cut test or peel test to check the adhesion between the coating and the aluminum fin to ensure that there is no peeling; perform a salt spray test and a mold culture test to evaluate the anti-corrosion and anti-mildew properties of the coating.
2. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: In the step 1, the concentration of the cleaning agent is 0.5%-1% non-ionic cleaning agent; the cleaning temperature is 60°C; the cleaning time is 5-10 minutes; the degreasing uses a degreasing agent, the degreasing agent is an organic solvent, and the immersion time is 5 minutes.
3. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: In the step 1, the dilute acid is sulfuric acid, and the concentration of the sulfuric acid is 10%-20%; the etching time of the sulfuric acid is 2-5 minutes, and the temperature is room temperature to 50°C.
4. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: In the step 2, an acid neutralizer is used, the acid neutralizer is 0.5% sodium hydroxide solution, and the flushing time is 5 minutes.
5. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: The cleaning expression in step 1 is: ; The degreasing expression is: ; The acid treatment expression is: 。 6. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: The deposition thickness of the coating in step 4 is calculated as: in: is the deposition thickness of the coating, unit: meter; It is a constant related to the coating properties, coating density and adhesion factors, unit: m² / A·s; is the current, unit: ampere; is the electrophoresis time, unit: second, s; It is the surface area of the aluminum fin, unit: square meter, m².
7. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: The current in step 4 is calculated by Ohm's law of voltage and resistance: ;in is the voltage, is the total resistance of the electrophoresis tank; Combined with the calculation of current, the coating deposition amount is expressed as: 。 8. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: The influence of temperature on the fixed rate in step 5 is calculated as follows: in: is the reaction rate constant; is the anterior factor; is the activation energy; is the gas constant; is the absolute temperature; The influence of water evaporation in step 5 is calculated as: in: For time Water quality at the time of is the initial water mass; is the evaporation rate constant; The time unit is seconds.
9. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: The thickness of the cured coating in step 5 is calculated as: in: is the final thickness of the coating after curing; is the thickness of the initial coating; The time for the curing process.
10. The electrophoretic coating process for aluminum fin heat exchanger according to claim 1, characterized in that: The mold culture test calculation in step 6 is: in: Fungal growth inhibition rate; is the number of mold in the control group; is the number of mold in the test group.
Citation Information
Patent Citations
Application of anti-corrosion and anti-mildew coating on heat exchanger fin, preparation method of anti-corrosion and anti-mildew coating and air conditioner heat exchanger
CN118357134A